In vitro transcription of bacteriophage phi 29 DNA: inhibition of early promoters by the viral replication protein p6. - Barthelemy, I (J Virol, 1989)
The effect of the phi 29 protein p6 on the in vitro initiation of transcription from the main phi 29 promoters was studied. Protein p6 interfered with the transcription from the early promoters C1 and C2, located at the right end of the phi 29 genome. Transcription initiated at the early promoters A1, A2b, and A2c and at the late promoter A3, located at the left region of the viral genome, was not affected by protein p6. These results suggest that protein p6 might play a dual role, acting as a negative modulator of some phi 29 early promoters apart from being a positive modulator of the viral DNA replication. IMAGES: